E. tapos yoghurt-a view from nutritional composition and toxicological evaluation - Naomi, Ruth; Mahmad Rusli, Rusydatul Nabila; Balan, Santhra Segaran; Othman, Fezah; Jasni, Azmiza Syawani; Jumidil, Siti Hadizah; Bahari, Hasnah; Yazid, Muhammad Dain (Multidisciplinary Digital Publishing Institute, 2022)
Elateriospermum tapos (E. tapos) is a natural tropical plant that possess a wide range of health benefits. Recent discovery proves that E. tapos extract is able to reduce weight, increase cognitive performance, and ameliorate anxiety and stress hormone. However, this extraction has not been incorporated into yoghurt, and no toxicity studies have been done previously to prove its safety. Thus, this study was aimed to formulate the ethanolic extracted E. tapos into yoghurt and access the toxicological effects on rodents. Forty female Sprague Dawley (SD) rats were used in this study and force fed with either one of the following doses of 250, 500, 1000, or 2000 mg/kg, while the control group received normal saline. The nutritional analysis result showed that the newly formulated yoghurt comprised 328 kJ of energy per 100 mL of servings, 3.6 g of fats, 8.2 g of carbohydrates, 2.7 g of total protein, and 1.2 g of fibre. The peak intensity of Lactobacillus species was observed at 1.6 × 105 CFU/g with a titratable acidity as lactic acid of 0.432 CFU/g, indicating the ability of the formulated yoghurt in stimulating the growth of Lactobacilli. In the experimental study, the E. tapos yoghurt in a single dose (2000 mg/kg) did not show any treatment related to toxicity in any of the rats observed in an additional 14 days. There were no changes in body weight, food and water intake, plasma biochemistry (ALT, AST, ALP, and creatinine), haematological products, and organ weights of the treated groups compared to the subacute control groups. Histological examination of all organs including liver, heart, and kidney were comparable to the control groups. In toto, oral consumptions of E. tapos yoghurt did not induce any adverse effects on rodents.